Combination of the insulator‐based dielectrophoresis and hydrodynamic methods for separating bacteria smaller than 3 μm in bloodstream infection: Numerical simulation approach. Issue 1 (21st November 2022) - Rizi, Farideh Salimian; Talebi, Shahram; Manshadi, Mohammad K D; Mohammadi, Mehdi
Abstract: Bloodstream infections have a high mortality rate with >80, 000 deaths per year in North America. The inability to detect pathogens quickly in the early stages of the infection causes high mortality. Such inability has led to a growing interest in developing a rapid, sensitive, and specific method for identifying these pathogens. The rapid detection of bloodstream infections requires the rapid and efficient separation of bacteria from the blood. But the problem is that the number of bacteria is much lower than other blood components. The blood culture step needs to be accomplished first for bacteria identification and antibiotic susceptibility testing. As the blood culture is time‐consuming, a method based on the insulator‐based has been presented that increases the number of bacteria by combining the blood culture method and increasing the concentration. In this model, the dielectrophoresis technique was utilized in a curved microchannel with a constriction for sorting three particle sizes including 9, 7–4 μm, as well as smaller than 3 μm. The results showed that the applied voltage and the channel dimensions affect separation efficiency. Suppose these values are properly selected (for example, a voltage of 110 V that was causing the maximum electric field of 200 V/cm). The proposed model can completely (100%) separate larger than 9 μm and smaller than 3 μm particles. The proposed model has simple geometry and is considered an appropriate technique for sorting all bacteria separation in bloodstream infection.